Influence of the Amount of Steel Fibers on Fracture Energy and Drying Shrinkage of HPFRCC - Weina Guo; Peng Zhang; Yupeng Tian; Bing Wang; Wan Ma (Advances in Materials Science and Engineering)
The fracture energy of the high-performance fiber-reinforced cement-based composite (HPFRCC) can be modified within wide limits by the variation of the amount of steel fibers added to the fresh mix. First of all, considering the actual engineering conditions in Qingdao, the materials commonly used in Qingdao were selected. The optimal reference mix proportion of the HPFRCC cementing material was proposed through determination of fluidity and flexural strength. Based on the optimal mix proportion, the uniaxial tensile, fracture, and dry shrinkage properties of HPFRCC with different steel fibers are systematically studied. Stress-strain diagrams of the different samples were measured under the uniaxial tensile test, wedge splitting test, and three-point bending test. The steel fiber content was varied between 0 and 200 kg/m3. The load bearing capacity and the fracture energy were determined experimentally. In addition, moisture loss as a function of time and shrinkage was determined in an environment of 20°C and 50% RH (relative humidity). The results indicate that the maximum load increases significantly in the HPFRCC series reinforced by 150 and 200 kg/m3 of steel fibers. Both have a hardening branch developed after the first crack deflection due to the high percentage of fibers bridging the crack surfaces. The load bearing capacity and fracture energy increased almost linearly with the steel fiber content. It was found that the three-point bending test is more applicable in measuring the fracture energy of HPFRCC than the wedge splitting test. The addition of steel fibers decreased the moisture diffusion and consequently the drying shrinkage of HPFRCC, and there was minimum weight loss and deformation when the steel fiber content was 150 kg/m3. The results obtained will be presented and discussed.